The criminology of place street segments and our understanding of the crime problem - Weisburd, David; Groff, Elizabeth (Elizabeth R.); Yang, Sue-Ming. (New York ; Oxford : Oxford University Press, 2013)
The authors present a new way of looking at crime by examining why specific streets in a city have specific crime trends over time. Reorienting the study of crime by focusing not on individuals and communities, but on small units of geography the authors identify a large group of possible crime risk and protective factors for street segments and an array of interventions that could be implemented to address them.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes bibliographical references and index.
Keywords: Criminology; Geographical offender profiling; Crime prevention